Fracture Toughness Improvement of Poly(lactic acid) Reinforced with Poly(ε-caprolactone) and Surface-Modified Silicon Carbide - Jie Chen; Tian-Yi Zhang; Fan-Long Jin; Soo-Jin Park (Advances in Materials Science and Engineering)
In this study, bio-based poly(lactic acid) (PLA)/polycaprolactone (PCL) blends and PLA/PCL/silicon carbide (SiC) composites were prepared using a solution blending method. The surface of the SiC whiskers was modified using a silane coupling agent. The effects of the PCL and SiC contents on the flexural properties, fracture toughness, morphology of PLA/PCL blends, and PLA/PCL/SiC composites were investigated using several techniques. Both the fracture toughness and flexural strength of PLA increased by the introduction of PCL and were further improved by the formation of SiC whiskers. Fracture surfaces were observed by scanning electron microscopy, which showed that the use of PCL as a reinforcing agent induces plastic deformation in the PLA/PCL blends. The SiC whiskers absorbed external energy because of their good interfacial adhesion with the PLA matrix and through SiC-PLA debonding in the PLA/PCL/SiC composites.